2019
DOI: 10.1177/2470547019879088
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Stress and Coping with DNA Methylation of Blood Pressure-Related Genes Among African American Women

Abstract: Background Exposure to psychosocial stress and employment of high effort coping strategies have been identified as risk factors that may partially explain the high prevalence of hypertension among African Americans. One biological mechanism through which stress and coping may affect risk of hypertension is via epigenetic modifications (e.g., DNA methylation) in blood pressure-related genes; however, this area remains understudied in African Americans. Methods We used data from the ongoing Intergenerational Blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…In a small study of mother-child pairs, Black mothers experiencing high parenting stress had significant modifications at 95 CpG sites, including the PARP-I gene, which plays a role in response to stress ( 137 ). A separate study among the same study sample identified CpG sites at blood pressure-related genes in relation to stress and coping mechanisms; however, the results did not remain significant after accounting for multiple testing ( 23 ). Unfortunately, both studies were limited in their power to detect associations due to small sample sizes, warranting more research in larger samples.…”
Section: Psychosocial Stressors and Dna Methylationmentioning
confidence: 98%
“…In a small study of mother-child pairs, Black mothers experiencing high parenting stress had significant modifications at 95 CpG sites, including the PARP-I gene, which plays a role in response to stress ( 137 ). A separate study among the same study sample identified CpG sites at blood pressure-related genes in relation to stress and coping mechanisms; however, the results did not remain significant after accounting for multiple testing ( 23 ). Unfortunately, both studies were limited in their power to detect associations due to small sample sizes, warranting more research in larger samples.…”
Section: Psychosocial Stressors and Dna Methylationmentioning
confidence: 98%
“…A prior study examining stress, coping and methylation of blood pressure-related genes in InterGEN, showed that stress overload and coping strategies were associated with epigenetic changes, though these relationships did not hold after accounting for multiple testing adjustment. 52 Additionally, stress and coping were not found to be significantly associated with blood pressure candidate genes. 52 This present analysis expanded on the previous study by employing an epigenome-wide approach to assess potential associations of stress overload with DNAm.…”
Section: Discussionmentioning
confidence: 96%
“… 52 Additionally, stress and coping were not found to be significantly associated with blood pressure candidate genes. 52 This present analysis expanded on the previous study by employing an epigenome-wide approach to assess potential associations of stress overload with DNAm. Other InterGEN analyses have also demonstrated the importance of chronic stressors such as neighborhood stress and experiencing racial discrimination and how exposure to such stressors negatively impact mental and physical health.…”
Section: Discussionmentioning
confidence: 96%
“…Some research suggests that African-American women may underreport stress due to cultural and societal norms that may facilitate maladaptive coping and difficulty acknowledging stress. 71 More research is needed on assessments of stress in this population and whether or not currently available tools may not perform ideally in this population to capture stress levels accurately.…”
Section: Discussionmentioning
confidence: 99%